Penguatan Karakter melalui Media Digital: Kolaborasi Guru, Orang Tua, dan Siswa dengan Canva dan Nearpod - Muhammad Arie Zulfan; Dien Nurmarina Malik Fadjar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to evaluate the effectiveness of the use of Canva and Nearpod digital platforms in supporting the strengthening of students' character at the elementary school level. Character education is a fundamental aspect in the formation of students' personalities who have integrity, toughness, and adaptability to the development of the times. In the digital era, interactive learning media is an important means to instill character values in a more interesting and contextual way. The method used is Classroom Action Research (PTK) which is carried out in two cycles, with the research subjects consisting of teachers, class V students, and students' parents. The learning process is designed to blend character education content with the use of Canva as a creative visual medium, as well as Nearpod as an interactive presentation tool that allows students to be active through online quizzes, assignments, and reflections. The results of the study showed a marked increase in students' learning motivation, attitude of responsibility, discipline, cooperation in groups, and the ability to make decisions independently. Parental involvement in digital learning also supports the consistency of character strengthening at home. However, the study also noted several challenges, such as the limitations of technological devices, unstable internet networks, and variations in students' and parents' digital literacy abilities. Recommended solutions include intensive training for teachers in the use of digital media, improved support facilities in schools, as well as a collaborative approach between teachers and parents. Thus, the integrated use of Canva and Nearpod not only supports mastery of academic materials, but also significantly strengthens students' character values holistically. This study is expected to be a reference in the development of digital learning innovations oriented towards character education at the elementary level.